THE INFLUENCE OF THE LEARNING PROCESS PSYCHOMOTOR IN CHILDREN WITH DOWN SYNDROM (Fiep Bulletin - online, 2016)
Children with Down syndrome have, as one of his most constant features, mental retardation, which complicates the importance of their education because there is need to provide effective means of quality education, meeting their needs and characteristics. Thus, psychomotor becomes an alternative in the processing of language acquisition, because it stimulates the motor and psychic, relevant factors in the writing process. Thus, the aim of this study is to analyze the influence of psychomotor skills in the learning process in children with Down syndrome. However, this relationship between language and motor skills in children with Down syndrome, was held from literature, in which he did not finish strong relationships, only the literacy process, but also in vocabulary and speech articulation.
Keywords: language - psychomotor - Down syndrome